VALIDITAS KETERANGAN AHLI DARI PENYIDIK DALAM PEMBUKTIAN KASUS UJARAN KEBENCIAN RAS DI MEDIA SOSIAL (STUDI PUTUSAN: NO.1105/PID.SUS/2017/PN JKT.UTR) - Hendra .; Dian Andriawan Daeng Tawang (Jurnal Hukum Adigama, 2018)
Expert’s Testimony is the information of a person who has special expertise for the purpose of examination in a criminal case and must be given in court. An expert must provide information for justice, as well as possible and according to knowledge in his area of expertise. The expert's testimony from the police is still questionable on the independence and justice of the defendant, the expert must be independent and fair in giving explanation there should be no influence from internal or external parties. There are still many expert testimonies from investigators who are highly doubtful of their independence and deemed inappropriate to be made expertly by academicians, but in the Criminal Procedure Code it is not clear whether the expert's testimony from the investigator is allowed or not. Therefore the author interested in conducting research related to the validity of expert testimony from investigators. The author conducted research with normative legal research methods supported by interviews are expected to help answer the research and the source of interviewed is from the academics and practitioners. In the absence of clear rules, the expert's testimony from the investigator will be the pros and cons but if it refers to the understanding and the main purpose of expert testimony in the Criminal Procedure Code, it is unlikely that the expert's expertise is allowed because it will not be free, independent.